Detection of Vertical Root Fractures Using Cone-Beam Computed Tomography in the Presence and Absence of Gutta-Percha - Ehsan Hekmatian; Mitra Karbasi kheir; Hossein Fathollahzade; Mahnaz Sheikhi (The Scientific World Journal)
Background. Vertical root fractures (VRFs) can significantly reduce dental prognosis. Cone-beam computed tomography (CBCT) offers better visualization of VRF than conventional radiography. However, gutta-percha creates artifacts in cone-beam CT (CBCT) images and reduces the diagnosis quality. The purpose of this study was to evaluate the accuracy of CBCT in detection of VRF in presence and absence of gutta-percha in canals. Materials and Methods. In this cross-sectional study, 50 extracted mandibular premolars were selected. After preparing the access cavity, canals were instrumented using step-back method, and gutta-percha #40 was placed afterwards. The fractures were created using electromechanical universal testing machine on 25 teeth. The teeth were randomly placed in dry mandibular dental sockets, and the first CBCTs were taken. Then the gutta-percha was removed, and the second CBCTs were taken. Results. The results of Kappa coefficient between two observers in roots with and without gutta-percha were 0.644 and 0.830, respectively (p value ≤ 0.001). The sensitivity and specificity of VRF diagnosis in assessing gutta-percha filled canals were 32% and 68% for the first observer, respectively (Kappa < 0.000, p value = 1.000), and 40% and 68% for the second observer, respectively (Kappa = 0.080, p value = 0.556). The sensitivity and specificity of VRF diagnosis in assessing the empty canals (without gutta-percha) were 72% and 96% for the first observer, respectively (Kappa = 0.680, p value ≤ 0/001), and 72% and 96% for the second observer, respectively (Kappa = 0.680, p value ≤ 0/001). Conclusion. The intracanal filling materials such as gutta-percha reduce the diagnostic ability of vertical root fractures. Hence, it is recommended to remove those materials from root canals before imaging to improve the diagnostic potential of CBCT.